Testing the Treatment Integrity of the Managing Cancer and Living Meaningfully Psychotherapeutic Intervention for Patients With Advanced Cancer - Koranyi, Susan; Philipp, Rebecca; Quintero Garzón, Leonhard; Scheffold, Katharina; Schulz-Kindermann, Frank; Härter, Martin; Rodin, Gary; Mehnert-Theuerkauf, Anja (Frontiers in Psychology, 2020)
Introduction The Managing Cancer and Living Meaningfully (CALM) therapy for patients with advanced cancer was tested against a supportive psycho-oncological counseling intervention (SPI) in a randomized controlled trial (RCT). We investigated whether CALM was delivered as intended (therapists’ adherence); whether CALM therapists with less experience in psycho-oncological care show higher adherence scores; and whether potential overlapping treatment elements between CALM and SPI can be identified (treatment differentiation). Methods Two trained and blinded raters assessed on 19 items four subscales of the Treatment Integrity Scale covering treatment domains of CALM (SC: Symptom Management and Communication with Health Care Providers; CSR: Changes in Self and Relationship with Others; SMP: Spiritual Well-being and Sense of Meaning and Purpose; FHM: Preparing for the Future, Sustaining Hope and Facing Mortality). A random sample of 150 audio recordings (75 CALM, 75 SPI) were rated on a three-point Likert scale with 1 = “adherent to some extent,” 2 = “adherent to a sufficient extent,” 3 = “very adherent.” Results All 19 treatment elements were applied, but in various frequencies. CALM therapists most frequently explored symptoms and/or relationship to health care providers (SC_1: n_applied = 62; 83%) and allowed expression of sadness and anxiety about the progression of disease (FHM_2: n_applied = 62; 83%). The exploration of CALM treatment element SC_1 was most frequently implemented in a satisfactory or excellent manner (n_sufficient or very adherent = 34; 45%), whereas the treatment element SMP_4: Therapist promotes acknowledgment that some life goals may no longer be achievable (n_sufficient or very adherent = 0; 0%) was not implemented in a satisfactory manner. In terms of treatment differentiation, no treatment elements could be identified which were applied significantly more often by CALM therapists than by SPI therapists. Conclusion Results verify the application of CALM treatment domains. However, CALM therapists’ adherence scores indicated manual deviations. Furthermore, raters were not able to significantly distinguish CALM from SPI, implying that overlapping treatment elements were delivered to patients.